The movement "Hirak" inspire Algerian protestor’s and set up new concepts: : hirakistes, dégagisme "rejection", and vendredir (e) …! - BENABID, Faïza; KETHIRI, Brahim (Journal of Human Sciences, 2023)
The cultural, social and political factors of linguistic variation combine with the unbridled development of the means of communication to make the French language a mosaic language in perpetual motion. It renews itself, and moves at every moment, as G. MOUNIN1 "writes in its lexicon in a relatively short period". This movement is especially visible in the use of the neologisms that we propose to examine in this article, which focuses on the operation of these new lexical units, integrated into the linguistic repertoire of Algerians in through: promising channels such as social networks, young people and mainly the press to bridge language gaps and describe new realities.